Mentoring Graduate Students Online: Strategies and Challenges - Pollard, Rhiannon; Kumar, Swapna (International Review of Research in Open and Distributed Learning, 2021)
The proliferation of online graduate programs, and more recently, higher education institutions’ moves to online interactions due to the COVID-19 crisis, have led to graduate student mentoring increasingly occurring online. Challenges, strategies, and outcomes associated with online mentoring of graduate students are of primary importance for the individuals within a mentoring dyad and for universities offering online or blended graduate education. The nature of mentoring interactions within an online format presents unique challenges and thus requires strategies specifically adapted to such interactions. There is a need to examine how mentoring relationships have been, and can best be, conducted when little to no face-to-face interaction occurs. This paper undertook a literature review of empirical studies from the last two decades on online master’s and doctoral student mentoring. The main themes were challenges, strategies and best practices, and factors that influence the online mentoring relationship. The findings emphasized the importance of fostering interpersonal aspects of the mentoring relationship, ensuring clarity of expectations and communications as well as competence with technologies, providing access to peer mentor groups or cohorts, and institutional support for online faculty mentors. Within these online mentoring relationships, the faculty member becomes the link to an otherwise absent yet critical experience of academia for the online student, making it imperative to create and foster an effective relationship based on identified strategies and best practices for online mentoring.